Desenvolvimento de dispositivo programável de movimento passivo contínuo para membros inferiores - Sperb, Daniel Quintana (2006)
This research presents the project of a programmable continuous passive motion device (CPM) for lower members, this equipment is known worldwide by the abbreviature C.P.M, which in the English language stands for continuous passive motion. The C.P.M devices allow the mobilization of articular segments on upper or lower members such as ankles, knees and hips, immediately after the surgery, making available the maintenance of the tissues that surround the articulation. The C.P.M that exist on the market are pre-programmed, that is, they do not offer flexible programming possibilities. Besides displaying the motivations referring to the theme of the research, as well as its application, this project also displays a literature review composed by foundations in the areas of physiotherapy, project, technology followed by a field research conducted aiming towards professionals specialized in injuries on lower members. The presented results show the application of numeric command technology making possible that the proposed functional model operates in a flexible way, providing countless programming possibilities to the user.